STRATEGIC ANALYSIS OF TOOLS/MEDIA COMBINATION FOR DISTANCE LEARNING IN SCIENCE COURSES - Muhammad Syazali; Muhammad Erfan; Lalu Wira Zain Amrullah; Hasnawati Hasnawati (PROGRES PENDIDIKAN, 2023)
Negative responses to the learning process and the high cost of buying quotas are problems that arise due to the implementation of online learning during PJJ. The purpose of this research is to analyze strategies for using a combination of distance learning tools/media that are effective and low-cost in the teaching-learning process in science courses. This survey research uses a closed questionnaire as a research instrument. Questionnaires were distributed to 112 PGSD students. The questions asked were 10 items related to network and internet access, and the PJJ tools used. The data obtained were analyzed using descriptive statistics. We found the fact that the University of Mataram has provided good e-learning for use in online learning. The vicon media and social media that are most frequently used sequentially are Google Meet (96.4%) and WA (99.1%). Therefore, the online tool/media that we recommend is the use of a combination of the three tools/media together with the surrounding environment as a Natural Laboratory in science learning. This recommendation is not only relatively cheaper in cost, but also has the potential to develop aspects of students' knowledge, attitudes and science process skills.